2006
DOI: 10.1139/z06-029
|View full text |Cite
|
Sign up to set email alerts
|

Resident beavers (Castor canadensis) do not discriminate between castoreum scent marks from simulated adult and subadult male intruders

Abstract: Subadult intruding beavers (Castor spp.) could be expected to pose a higher threat than adults to territory holders because, unlike adults who usually own a territory, subadults need to acquire a territory and a mate to reproduce successfully. We tested the responses of territorial beavers (Castor canadensis Kuhl, 1820) to simulated intrusions by adult and subadult males. Territorial intrusion was simulated through scent playback experiments that exposed residents to castoreum from adult and subadult strangers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…It is also noteworthy that the observed and simulated ranges matched more closely for longdispersal distances (i.e., > 80 km for the beaver and > 3 km for the African clawed frog). For the Eurasian beaver, this dispersal distance is consistent with maximal empirical estimates of dispersal on the Loire River (Fustec et al, 2001), and is in the higher range of commonly measured dispersal distances in other waterways for this species (Saveljev et al, 2002) or for the Canadian beaver, Castor canadensis (Sun et al, 2000). For the African clawed frog, the colonization front has been estimated to shift at a speed of 1km/year (Fouquet and Measey, 2006).…”
Section: Forecasting the Colonization Of River Networksupporting
confidence: 82%
“…It is also noteworthy that the observed and simulated ranges matched more closely for longdispersal distances (i.e., > 80 km for the beaver and > 3 km for the African clawed frog). For the Eurasian beaver, this dispersal distance is consistent with maximal empirical estimates of dispersal on the Loire River (Fustec et al, 2001), and is in the higher range of commonly measured dispersal distances in other waterways for this species (Saveljev et al, 2002) or for the Canadian beaver, Castor canadensis (Sun et al, 2000). For the African clawed frog, the colonization front has been estimated to shift at a speed of 1km/year (Fouquet and Measey, 2006).…”
Section: Forecasting the Colonization Of River Networksupporting
confidence: 82%
“…The models for short‐lived animals did not explain the finding that 23, 57 and 1012 mo old female voles did not differ in the amount of scent marks they depositing in an arena that was previously marked by an opposite‐sex conspecific. The frequency of scent marking in adult North American beavers was also not affected by their age (Herr et al. 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies demonstrated that scent marking was higher at or near puberty and then declined as individuals aged in gray mouse lemurs, honey badgers, and Mongolian gerbils (Arkin et al 2003;Begg et al 2003;Aujard & Né moz-Bertholet 2004;Cayetanot et al 2005). One study reported that the frequency of scent marking was not affected by age after North American beavers reached puberty (Herr et al 2006). Interestingly, many of the studies that examined the effects of age on scent marking focused on the behavior of individuals in areas that did not contain the marks of opposite-sex conspecifics.…”
Section: Ethology 24mentioning
confidence: 99%
See 1 more Smart Citation